Effect of The Addition of Hyacinths as Feed to Increase The Production of Earthworms (Lumbricus rubellus) - Rohani Rohani; Karnan Karnan; Mohammad Liwa Ilhamdi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Water hyacinth (Eichhornia crassipes) is one of Indonesia's wild plants which is considered a weed because of its rapid growth that can cause environmental problems. Generally, water hyacinth control is carried out physically/conventionally by throwing it away or burning it, causing new environmental problems. Water hyacinth has a high organic matter content, therefore water hyacinth can be used as an alternative feed to increase the production of earthworms. This study aims to determine the effect of adding water hyacinth as feed to increasing the production of earthworms (Lumbricus rubellus).This study aims to determine the effect of adding water hyacinth as feed to increasing the production of earthworms (Lumbricus rubellus). The research was conducted in the Dasan Dao hamlet, Ranggagata Village, Southwest Praya District, Central Lombok Regency, in the researcher's private house for 60 days. This type of research is an experimental research. The research design used was a completely randomized design with 4 treatments and 4 replications. Treatments were P0 (0 grams of water hyacinth), P1 (50 grams of water hyacinth), P2 (100 grams of water hyacinth), P3 (150 grams of water hyacinth). Parameters observed were the number and weight of earthworms. The results showed that the treatment had a significant effect on the weight and number of earthworms (P<0.05). The results of the treatment on the number of earthworms P0;P1;P2;P3 were 84;93.75;117.25;127.5 and the weight of earthworms was 85;102.5;118.75;124.75. The highest number and weight of earthworms were found in the P3 treatment (150 g of water hyacinth). The conclusion of this research is the addition of water hyacinth as feed can increase the number and weight of earthworms.